Quantification of Young's modulus of kaolin, sodalite and nanocomposite based polycaprolactone/sodalite using atomic force microscopy - Kenza Elhachemi; Habib Khellafi; Mostefa Bendouba; Abdelkader Djebli (Materials Research Express, 2024)
The mechanical properties of clays, zeolite, and nanocomposite reinforced by these minerals are unique regarding their states and functions. Nevertheless, it is difficult to acknowledge the degrees of mechanical properties because of the nano-size of these materials and the broad distribution of these properties. This study aims to the quantification of Young’s modulus of three materials, namely kaolin, sodalite, and nanocomposite PCL/sodalite using the atomic force microscope (AFM). The Oliver-Pharr and Hertz models are considered for this quantification. The values of these modulus ranging from 11.19 to 69.15 GPa for the Oliver-Pharr model and 10.89 to 127.09 GPa for Hertz model (kaolin). On the other side, the Young’s modulus of sodalite varies between 69.02 and 12.01 GPa for the Hertz and the Oliver-Pharr models (sodalite). This modulus for nanocomposite ranges from 1.75 to 6.66 GPa and 1.63 to 45.36 GPa for the cited models, This research presents a simple and easy way to calculate this modulus without resorting to Nano-indentation. Moreover, this technique was also used to investigate the morphology of these materials. Therefore, it was deduced that the mechanical and morphological properties of the studied materials are completely different, especially nanocomposites, even though they have the same origin, which is kaolinite.